TEST OF BLOOD DISEASE BACTERIUM (BDB) TRANSMISSION BY POTENTIAL INSECT VECTORS - Sahetapy, Betty; Maryana, Nina; Manuwoto, Syafrida; H. Mutaqin, Kikin; Latumahina, Fransina (JURNAL HAMA DAN PENYAKIT TUMBUHAN TROPIKA, 2020)
Blood disease bacterium (BDB) is one of the important diseases in banana and a major obstacle in developing and increasing banana production in Indonesia. The purpose of this study was to prove the ability of the Drosophilidae insect as a vector in transmitting BDB. The research was conducted at the Insect Biosystematics Laboratory and Plant Bacteriology Laboratory, Department of Plant Protection, Faculty of Agriculture, IPB University. Drosophilidae insects were taken from the field and then reared in laboratory by being fed with ripe bananas to obtain offspring that are free from diseases or pathogens. Imago of the Drosophilidae from rearing was fed by inoculum sources which was infected banana, then inoculated into healthy plants. The plants used were healthy and flowering, heliconia. The results showed that the Drosophilidae insects were able to transmit BDB to heliconia plants that showed symptoms, brownish flower colors and falling flower crowns. Detection of BDB isolated from flower parts and the inside parts of the insects used in transmission test using the PCR method showed positive results.